Ah Jongumsobomvu! an analysis of the commemorative statues of Nkosi Jongumsobomvu Maqoma - Matose, Kineiloe (Department of Historical Studies, 2025)
Nkosi Jongumsobomvu Maqoma, a nineteenth-century anti-colonial resistance figure, has become an increasing presence in the South African cultural landscape, a process that culminated in the renaming of Fort Beaufort to KwaMaqoma in March 2023. This minor dissertation examines two commemorative statues of Nkosi Maqoma with the aim of unpacking the very different local and national political projects in which his memory has recently been mobilised. The first statue, commissioned by the Eastern Cape government through independent heritage project Zemk'iinkomo: uNkosi Jongumsobomvu Maqoma, is a concrete representation of Maqoma initially designed to stand opposite the statue of Queen Victoria in Qonce. Instead, it was erected on the mountain of Ntaba kaNdoda in 2015, a site of particular significance to both Maqoma and the history of the amaJingqi. Here, thirty-eight years after Maqoma's supposed bones were reinterred on the mountain as part of an attempt to turn him into the father of the Ciskean Bantustan and create a Ciskean national identity, Maqoma was once again mobilised by local political groups in defence of a disputed claim to traditional authority. The second statue is a bronze of Maqoma found amongst more than a hundred other bronze statues as part of Dali Tambo's Long March to Freedom Exhibition. This national memorial project is currently situated next to Canal Walk (a shopping and entertainment precinct) in Cape Town. In this Exhibition, Maqoma is portrayed as part of a linear history of resistance to apartheid that culminated in African National Congress (ANC) rule. The history, figurative and literal mobility of these two heritage-tourism projects opens a window to consider the complex questions and contestations of memory, heritage-tourism, and politics in which Nkosi Maqoma's statues are currently embroiled.